PEMBERDAYAAN SANTRI MELALUI PENGEMBANGAN SDM, MANAJEMEN KEUANGAN DAN PEMASARAN KREATIF - Irfan Rizka Akbar; Aldi Arsyad; Dafa Alfareza; Desika Jayanti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Student Creativity Program (PKM) is a form of community service aimed at providing a real contribution to improving the quality of human resources. This PKM activity was conducted under the theme “Empowering Islamic Boarding School Students through Human Resource Development, Financial Management, and Creative Marketing.” The program was motivated by the importance of enhancing students’ competencies so that they not only possess strong religious knowledge but also acquire skills that support independence and competitiveness in the modern era. Human resource development, financial management skills, and an understanding of creative marketing are essential aspects that students need to face future social and economic challenges.The implementation methods included socialization, presentations, interactive discussions, simulations, and question-and-answer sessions involving active participation from all participants. Human resource development materials focused on improving communication skills, leadership, teamwork, and self-development. Financial management materials emphasized effective and responsible financial management, while creative marketing materials provided insights into innovative marketing strategies and the use of digital media as promotional tools.The results of the activity showed an increase in participants’ understanding of the importance of human resource development, proper financial management, and creative marketing in supporting independence and productivity. The program also increased students’ motivation to develop their potential and utilize available opportunities more effectively. Through this activity, students are expected to become independent, creative, productive, and highly competitive individuals in the face of rapid social and economic changes.